Demographic analysis for article Hurricane-induced demographic changes in a nonhuman primate population - Hernández-Pacheco, Raisa; Morcillo, Dana O; Steiner, Ulrich K; Ruiz-Lambides, Angelina V; Grayson, Kristine L (Dryad, 2020)
Major disturbance events can have large impacts on the demography and
dynamics of animal populations. Hurricanes are one example of an extreme
climatic event, predicted to increase in intensity due to climate change,
and thus expected to be a considerable threat to population viability.
However, little is understood about the underlying
demographic mechanisms shaping population response following these extreme
disturbances. Here, we analyze 45 years of the most comprehensive
free-ranging nonhuman primate demographic dataset to determine the effects
of major hurricanes on the variability and maintenance
of long-term population fitness. For this, we use
individual-level data to build matrix population models and perform
perturbation analyses. Despite reductions in population growth
rate mediated through reduced fertility, our study reveals a
demographic buffering during hurricane years. As long as survival does not
decrease, our study shows that hurricanes do not result in detrimental
effects at the population level, demonstrating the unbalanced contribution
of survival and fertility to population fitness in long-lived animal
populations.
The demographic dataset of Cayo Santiago rhesus macaques was shared by the
Caribbean Primate Research Center, University of Puerto Rico.
This folder contains all the required data and codes to reproduce the main
study results. Codes were built in R version 3.5.1. These codes use
packages “popbio”, “tidyverse”, “ggplot2”, “scales”, and “gamm4” for
demographic data management and analysis. The data contains the following:
Morcillo_et_al_nonhurricane_transitions.csv contains every individual
transition during non-hurricane years; including age and stage at time t
and fate or stage at time t+1. Morcillo_et_al_hurricane_transitions.csv
contains every individual transition during hurricane years; including age
and stage at time t and fate or stage at time t+1.
Morcillo_et_al_nonhurricane_bootstrap.csv contains the bootstrap
transition matrix for a non-hurricane year.
Morcillo_et_al_hurricane_bootstrap.csv contains the bootstrap transition
matrix for a hurricane year. Morcillo_et_al_annual_matrices.RData contains
annual transition matrices from 1973 to 2018.
Morcillo_et_al_gamm_model.RData contains the generalized additive mixed
top model output Specifically, the codes provide calculations for: Mean
matrix populations models for non-hurricane and hurricane years from
individual-level transition data. Eigen analysis for matrix models Life
table response experiment Bootstrap and Kolmogorov-Smirnov test
Generalized additive mixed model Figures